Technology-based financial management transformation for effective strategic decision making - William S. Limoa; Agus Arman (Lentera Negeri, 2026)
The rapid development of digital technology has transformed financial management practices and strategic decision-making processes in modern organizations. Technologies such as cloud computing, enterprise resource planning systems, big data analytics, and artificial intelligence enable organizations to process financial information more efficiently, improve transparency, and support data-driven strategic decisions. Therefore, this study aims to analyze the role of technology-based financial management transformation in improving the effectiveness of strategic decision-making within organizations. This research employs a qualitative approach using a literature review design. Secondary data were collected from peer-reviewed journals, books, conference proceedings, and research reports obtained from academic databases including Google Scholar, Scopus, and ScienceDirect. The findings reveal that digital financial transformation enhances operational efficiency, financial transparency, predictive financial analysis, and organizational competitiveness through the integration of financial data analytics and automated financial systems. However, the study also identifies several critical challenges, including cybersecurity vulnerability, algorithmic bias, technological dependency, and organizational inequality. The study concludes that effective digital financial transformation requires not only technological adoption but also ethical governance, digital resilience, and strategic organizational adaptation.